ADAPTASI ALAT TES GOODENOUGH-HARRIS DRAW- A- MAN TEST UNTUK MENGUKUR KEMATANGAN INTELEKTUAL PADA ANAK-ANAK USIA 7 SAMPAI DENGAN 11 TAHUN DI JAWA TIMUR - Siti Fatimah; Sri Weni Utami; Diantini Ida Viatrie (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
The results of the studyadaptation of Goodenough-Harris Draw a Man Testshowed that the intellectual maturity data in the children aged 7 to 11 years old. The item validation test on the male drawing scale had a range of .112 to .602 while on the female drawing scale had a range of .103 to .530 showed that all the items contained in each scale were valid. Moreover, the internal consistency reliability test Cronbach Alfa demonstrated that the male drawing scale obtained reliability of .920 while the female drawing scale obtained reliability of .867. This test tool also had a guideline made in detail, consisting of attachment of the test tool, instruction of the test administration, how to use test tool, testing purposes, norms, scoring and way of interpretation..Thus, the psychologists and psychological scientists then can take further steps to make further decisions on the subject subjected to the tests. Future studies are expected to have more diverse age ranges and subjects and have external validity and reliability so that so that the adaptation of Goodenough-Harris Draw-a-Man Test will have a better quality before it spreads widely.